2019
DOI: 10.4025/actasciagron.v42i1.42973
|View full text |Cite
|
Sign up to set email alerts
|

Soybean macronutrient availability and yield as affected by tillage system

Abstract: The effect of tillage system (NT-no tillage; CT-conventional tillage; MT-minimum tillage; and NT/scarification, every three years) on soybean nutrient availability and yield was evaluated on Oxisol after 12 years of cultivation. Soil samples were collected at depths of 0.00-0.05, 0.05-0.10, and 0.10-0.20 m and were analyzed for P, K, Ca, Mg, carbon (C), organic matter (OM), pH value, potential CEC, base saturation (BS%), and number of semiquinone organic radicals. The macronutrient concentration in the leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The absence of response due to MT can be attributed to the lack of compacted soil layers capable of limiting soybean development, as also observed by Moreira et al (2019) and Santos et al (2019). A similar result was found by Secco et al (2009) and Franchini et al (2012),…”
Section: Soybean Yieldsupporting
confidence: 73%
See 1 more Smart Citation
“…The absence of response due to MT can be attributed to the lack of compacted soil layers capable of limiting soybean development, as also observed by Moreira et al (2019) and Santos et al (2019). A similar result was found by Secco et al (2009) and Franchini et al (2012),…”
Section: Soybean Yieldsupporting
confidence: 73%
“…There was also a reduction of Ca in M/O and K and P in M and M+B systems in depth (0.1-0.3 m) with MT (Table 5). Results from Moreira et al (2019), also showed a reduction of some nutrients, in the case of P reduction, the authors attributed to increased adsorption of P in Fe and Al oxides as chiseling was performed for 12 years, causing soil disturbance. The results of these interactions show the importance of using a diversified cropping system in the off-season (e.g.…”
Section: Soil Chemistrymentioning
confidence: 96%
“…Compared to CT, mineral element accumulation 56 and root density 57 were better under CA. Besides, the higher soil moisture in conservation agriculture increases the solubility and penetration of mineral elements into a plant, 58 , which may explain the increase of P, K and Na in durum wheat under CA than CT in our experiment (Table 2). It is well known that mineral element 59 and TPC 60 are influenced by the environment, cultivar and agronomic management interactions.…”
Section: Resultsmentioning
confidence: 74%
“…This free radical signal has been attributed to semiquinones radicals (Saab and Martin-Neto, 2008;Sajfutdinov et al, 2001), lignin, phenols, oxidation of fatty acids detectable in some vegetables (Yarbasi et al, 2011) as interactions with peroxides. The semiquinone free radicals are directly associated with the humification of some substances as well as with soil-organic minerals (Moreira et al, 2019;Saab and Martin-Neto, 2008).…”
Section: Resultsmentioning
confidence: 99%